Early literacy footprints: analysis of elementary school students' initial reading abilities using Early Grade Reading Assessment (EGRA) - Safitri, Novi; Heryani, Rina; Hadiapurwa, Angga; Sujana, Atep (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2026)
Low initial reading skills are an indication of low student literacy. This research aims to analyze the early reading skills of Phase A students, which includes grades 1 and 2 of elementary school. The research used a descriptive qualitative method, involving 122 students from two elementary schools in Garut Regency, aged 6 to 8 years old. The instrument used in this study was the Early Grade Reading Assessment (EGRA) reading test. The results of the study showed that 68% of students in Phase A had early reading skills in the category of needing guidance. Meanwhile, 6.6% of students were in the sufficient category, and 25.4% were in the good category. Based on EGRA indicators, letter recognition ability has a percentage of 55.15%, syllable reading ability 48.76%, word reading 41.49%, listening comprehension 34.44%, fluency 31.87%, and reading comprehension 16.53%. Thru analysis of the implementation of the EGRA test, students' reading abilities can be mapped more deeply, allowing teachers to take further action appropriate to the needs of each student. This finding is expected to serve as a basis for schools to design more effective learning strategies to improve student literacy in elementary schools.